(untitled) (Estudios digital, 2020)
Recently, migratory movements - particularly those involving large numbers of people who have come to Europe seeking to become refugees - have given rise to a kind of social discourse associated with "populist nationalism". At times this type of discourse, by generalizing and normalizing at the social level, has given rise to the emergence of a "culture of fear" which, as an articulated system of meaning and significance, can be examined from a sociosemiotic perspective, paying special attention to perceptive and interpretative processes supported by the imaginary dichotomy between a "we" and a "they" that occur both individually and collectively. This article examines the "culture of fear" that emerges around cultural diversity -specifically associated with migration- from such a theoretical perspective, in order to make a contribution both to the literature on cultures of fear, as well as to the debate on the risks their propagation and normalization pose to democratic societies.